Analisis Quality of Service Jaringan Wireless untuk Teknologi Streaming - Rudi Yanto; Dedy Irfan; Asrul Huda (Universitas Hamzanwadi, 2022)
Wireless network services can be known for their quality with the Quality of Service (QoS) method. This method can measure the quality of streaming services in terms of throughput, delay, packet loss, and jitter. The purpose of this study was to analyze wireless network QoS for streaming technology. This type of research is quantitative with observation methods using the Wireshark application and compared with TIPHON standards. The target of the ICONNET ISP wireless survey on Jalan Nusantara km. 13 Tanjungpinang Timur District. The parameters for measuring QoS use four parameters, namely throughput, delay, packet loss, and jitter. Our findings show that the throughput of obtaining index value is 3.67 and is at a good level. Furthermore, the delay value has an average index of 4 with the best level. Meanwhile, the jitter obtained an index value of 3 at a good level, while the packet loss value obtained an index of 3.3 and had a good level. Based on the results of this study, the quality of ICONNET ISP wireless network services when accessing streaming technology shows data speed instability, data delays, and lost data packets. However, the network quality is still in the